Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2013
DOI: 10.1145/2470654.2470707
|View full text |Cite
|
Sign up to set email alerts
|

Exploring personality-targeted UI design in online social participation systems

Abstract: We present a theoretical foundation and empirical findings demonstrating the effectiveness of personality-targeted design. Much like a medical treatment applied to a person based on his specific genetic profile, we argue that theorydriven, personality-targeted UI design can be more effective than design applied to the entire population. The empirical exploration focused on two settings, two populations and two personality traits: Study 1 shows that users' extroversion level moderates the relationship between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 70 publications
0
28
0
Order By: Relevance
“…In addition to measuring the volume of participation and member satisfaction, research has also produced usability metrics and design recommendations for evaluating and developing user interfaces (Brandtzaeg & Heim, 2008;Maloney-Krichmar & Preece, 2005;Nov, Arazy, López, & Brusilovsky, 2013;Raghavun, 2011;Sahib & Vassileva, 2009). Maloney-Krichmar and Preece (2005) have identified a number of success metrics relating to usability and policy; instead of effective moderation they suggest the supporting of group norms, so that the groups can become self-moderating.…”
Section: Conceptualizing User Participationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to measuring the volume of participation and member satisfaction, research has also produced usability metrics and design recommendations for evaluating and developing user interfaces (Brandtzaeg & Heim, 2008;Maloney-Krichmar & Preece, 2005;Nov, Arazy, López, & Brusilovsky, 2013;Raghavun, 2011;Sahib & Vassileva, 2009). Maloney-Krichmar and Preece (2005) have identified a number of success metrics relating to usability and policy; instead of effective moderation they suggest the supporting of group norms, so that the groups can become self-moderating.…”
Section: Conceptualizing User Participationmentioning
confidence: 99%
“…Some differences have been detected, not only in the amount of use but also concerning what people do online. Extroverts may spend less time online but are more prone to social networking, sharing and voicing their opinions, whereas those high in neurotic traits look for a sense of belonging (Nov et al, 2013). Findings by Cullen and Morse (2011) show that individuals high in neuroticism were less likely to actively participate in the online activity of the community, and motivations for participating varied according to personality trait, as those high in agreeableness were motivated by helping others whereas the main motivation for those high in conscientiousness was finding useful information.…”
Section: Personality Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose MT as our experimental platform as it allowed us to perform more iterations quickly and progressively to test our hypotheses on a diverse subject pool. In conducting research based on crowdsourced self-reported measures, we draw on an emerging research trend which demonstrates the viability of this approach [19,27]. For instance, Paolacci et al [32] compared results of classic experiments in judgment and decision-making using traditional and crowdsourcing methods and found that participants behave consistently.…”
Section: Participants and Apparatusmentioning
confidence: 99%
“…Two recent papers we explored the effectiveness of personality-targeted design Nov, Arazy, Lopez, and Brusilovsky, 2013). For example, they showed how users' extroversion levels determine their response to a particular design intervention (manipulating an indicator presenting the number of past visitor in a social recommender system).…”
Section: Resultsmentioning
confidence: 99%